2009
DOI: 10.1007/s12571-009-0037-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving food security through agricultural research and development in Timor-Leste: a country emerging from conflict

Abstract: Food security, Timor-Leste, Agricultural research, On-farm evaluation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…Many introduced genotypes of maize, peanut, sweet potato, cassava and irrigated rice produced much higher yields than local cultivars or landraces, and some have proved quite acceptable to local growers and consumers. For each crop, several genotypes were broadly adapted with good yields across sites, a result confirmed by the high adoption rates of the varieties by participating farmers (Borges et al 2009). In order to select 'elite' genotypes for further evaluation on farms, a Farmer Participatory Research approach has been used since [2005][2006].…”
Section: Varietal Selection To Improve Crop Productivitymentioning
confidence: 81%
See 2 more Smart Citations
“…Many introduced genotypes of maize, peanut, sweet potato, cassava and irrigated rice produced much higher yields than local cultivars or landraces, and some have proved quite acceptable to local growers and consumers. For each crop, several genotypes were broadly adapted with good yields across sites, a result confirmed by the high adoption rates of the varieties by participating farmers (Borges et al 2009). In order to select 'elite' genotypes for further evaluation on farms, a Farmer Participatory Research approach has been used since [2005][2006].…”
Section: Varietal Selection To Improve Crop Productivitymentioning
confidence: 81%
“…Since its inception, 'Seeds of Life' has been testing and introducing new genotypes of the major staple field crops: maize, rice, cassava, sweet potato and peanuts (Borges et al 2009 'Seeds of Life' has added mungbeans and temperate species such as, wheat, barley, potato and climbing bean Phaseolus spp. to the varieties being tested.…”
Section: Varietal Selection To Improve Crop Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to many other studies, which have focused on technical barriers to food insecurity (see for example Molyneux et al, 2012;Borges et al, 2009). It also explores the concepts and principle of food sovereignty as a possible pathway to reimagining the current food system that can cater for all Timorese people currently and under climate change.…”
Section: Research Questionsmentioning
confidence: 97%
“…In Timor-Leste, despite a long tradition of rice cultivation in some parts of the country (see Metzner, 1977;Fox, 1991Fox, , 2003bShepherd & McWilliams, 2013) and many reports and government documents (Borges et al, 2009;RDTL, 2011) that refer to rice as a staple food, rice has not always been a staple for all Timorese. A wide range of stories relayed during interviews in this study indicated that many people only started consuming rice during the Indonesian occupation, while others underscored that even today, at a heavily subsidised price, they cannot afford to have it as their main food type.…”
Section: Rice As Foreign Foodmentioning
confidence: 99%